The discourse of drug use in Egypt: an interdisciplinary exploratory study - Gutierrez, Alejandro (AUC Knowledge Fountain, 2015)
This thesis sets out to better understand how Egyptian society constructs and labels the ‘deviant’ behavior of drug use. However, it is not about drugs per se, it is about scrutinizing the complex process through which Egyptian society encounters, experiences, and regulates behavior. Through an interdisciplinary approach, it builds an alternative and critical understanding of a stigmatized group of individuals by describing how they shape or are shaped by the dynamic system in which they exist. Thus, it creates a conversation between the structures of power that regulate the moral economy of society on the one hand and individuals practicing a role with their substance use on the other. It explores the structural power that disciplinary mechanisms have over ‘deviant behavior’, while simultaneously illustrating that ‘deviant drug users’ are judged according to a variety of unique circumstances and spectrum of acceptability. While some are successfully stigmatized for violating norms, others are able to retain their autonomy and shape their own rules and value systems outside the judgment of mainstream society. So, by using drug use as a lens to examine society, this thesis analyzes the fluidity of power within society in this context and also the ambiguity of behavior within different times and spaces. Ultimately, this thesis shows that deviant behavior like drug use is essential to any society that designates boundaries and rules. For how do individuals know what roles, interactions, behavior, value systems, are legitimate if society doesn’t create a ‘deviant other’ whose transgressions teach right from wrong, lawful from unlawful, and the acceptable from the unacceptable.